Evaluation of different methods of glycan enrichment to their subsequent MS identification - Kondrashchenko, Iryna (Jihočeská univerzita, 2020)
The main aim of this thesis was to evaluate different parameters during the sample preparation steps (such as enrichment of glycoproteins, release, purification and modification of glycans) to enable better MS identification of glycans released from different ticks related samples.
Evaluation of different methods of glycan enrichment to their subsequent MS identification
Keywords: Glycan; glycoprotein; glycomics; mass spectrometry; matrix-assisted laser desorption/ionization; electrospray ionization; tick cell line.; Glycan; glycoprotein; glycomics; mass spectrometry; matrix-assisted laser desorption/ionization; electrospray ionization; tick cell line.